OHMLY: Development and Application of an Arduino-Based Educational Kit for Teaching Ohm's First Law in Youth and Adult Education - Carvalho, Wendresson; Alves, Melquisedeque; Burlamaqui, Akynara; Burlamaqui, Aquiles (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
This article presents the results of a master's research project that investigated the effectiveness of Educational Robotics integrated into physics instruction to enhance the understanding of Ohm's First Law among Youth and Adult Education (YAE) students in a public school located in the city of Extremoz, state of Rio Grande do Norte, Brazil. Using Ausubel's Theory of Meaningful Learning and the Design Science Research (DSR) methodology, an Arduino-based educational kit was developed and implemented. Through hands-on activities, the study aimed to promote student engagement by relating theoretical concepts to practice and everyday life, addressing challenges commonly faced by this group. The results indicate that the use of Educational Robotics, combined with active methodologies, contributes to more meaningful and motivating learning experiences in physics education.